2014
DOI: 10.1186/1743-8977-11-15
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity assessment of zinc oxide nanoparticles using sub-acute and sub-chronic murine inhalation models

Abstract: BackgroundAlthough ZnO nanoparticles (NPs) are used in many commercial products and the potential for human exposure is increasing, few in vivo studies have addressed their possible toxic effects after inhalation. We sought to determine whether ZnO NPs induce pulmonary toxicity in mice following sub-acute or sub-chronic inhalation exposure to realistic exposure doses.MethodsMice (C57Bl/6) were exposed to well-characterized ZnO NPs (3.5 mg/m3, 4 hr/day) for 2 (sub-acute) or 13 (sub-chronic) weeks and necropsied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
119
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(129 citation statements)
references
References 49 publications
(85 reference statements)
6
119
1
3
Order By: Relevance
“…Seiffert et al [27] conducted an intratracheal instillation test of silver nanoparticles, and the exposure induced a transient KC concentration in BALF, while the chemokine expression pattern was accompanied by neutrophil influx in the lung. An inhalation exposure of ZnO nanoparticles with low toxicity did not induce neutrophil influx or an increase the concentration of KC in BALF [28].…”
Section: Endpointsmentioning
confidence: 80%
“…Seiffert et al [27] conducted an intratracheal instillation test of silver nanoparticles, and the exposure induced a transient KC concentration in BALF, while the chemokine expression pattern was accompanied by neutrophil influx in the lung. An inhalation exposure of ZnO nanoparticles with low toxicity did not induce neutrophil influx or an increase the concentration of KC in BALF [28].…”
Section: Endpointsmentioning
confidence: 80%
“…27 Studies reported that ZnO NPs cause no toxicity to human cells and only low subchronic toxicity to rodents. [28][29][30] Furthermore, a previous study using Drosophila had reported no toxicity observed upon the ingestion of ZnO NPs. 21 On the other hand, another earlier study assessing the genotoxicity and oxidative stress induced by ZnO NPs in Drosophila showed a weak genotoxicity of ZnO NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is difficult to predict the toxicological behavior of NPs in living organisms by in vitro models alone. 145,146 There are still many unanswered questions concerning nanoneurotoxicity. For instance, after bypassing the BBB, where do NPs go?…”
mentioning
confidence: 99%